2021
DOI: 10.1111/1346-8138.16181
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of circulating neutrophil extracellular traps, interleukin (IL)‐8, IL‐22, and vascular endothelial growth factor in patients with venomous snake mamushi (Gloydius blomhoffii) bites

Abstract: Mamushi bites cause swelling and pain that extend from the bitten site. The coagulopathic, anti‐coagulopathic, and vasculopathic actions of mamushi venom result in various laboratory abnormalities, occasionally with muscular, renal, and other organ damage. We investigated the serum biomarkers that were associated with the pathogenesis of mamushi bites, focusing on markers related to tissue‐damage and neutrophil activation. Twenty patients (one case of grade 2, 13 cases of grade 3, and six cases of grade 4 of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study, no significant correlation between CitH3 and neutrophil counts was observed. In our previous study, however, there was a correlation between CitH3 and neutrophil counts in patients with mamushi bites 11 . This suggests that PPP is more focal inflammation than mamushi bites that systemically activate neutrophils.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, no significant correlation between CitH3 and neutrophil counts was observed. In our previous study, however, there was a correlation between CitH3 and neutrophil counts in patients with mamushi bites 11 . This suggests that PPP is more focal inflammation than mamushi bites that systemically activate neutrophils.…”
Section: Discussionmentioning
confidence: 64%
“…Of the more than 3000 known snake species, approximately 200 species (i.e., 15%) are considered dangerous because their bites can be fatal [ 9 , 10 ]. Bites from venomous snakes can cause a wide range of symptoms, from mild symptoms such as respiratory difficulties, headaches, and speech impairment, to severe symptoms including muscle, kidney, and organ damage, potentially leading to death [ 11 , 12 ]. Some venomous snakes tend to ambush from rock crevices, tree roots, or low shrubs, resulting in unexpected snakebite incidents, particularly in mountainous terrain with various landscape features [ 5 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%